The Impact of the Green and Digital Transition on Regional Cohesion in Europe - Ambre Maucorps; Roman Römisch; Thomas Schwab; Nina Vujanović (Intereconomics, 2023)
Closing the prosperity gap between regions has always been a key political aspiration of the European Union - and cohesion policy is the primary means to achieve that goal. Europe is currently undergoing a digital and green transition that is drastically changing the way its economy works. How well prepared are regions to capitalise on the twin transition? What impact will it have on regional cohesion in Europe? We find that greening and digitalising the economy will likely widen the gap between rich and poor regions in the European Union.
Keywords: R11; O21; 330; economic adjustment; regional development; digitalization; EU regional policy; Wirtschaftliche Anpassung; Regionalentwicklung; Digitalisierung; EU-Regionalpolitik